Identidade afro-brasileira e moda - Harger, Patrícia Helena Campestrini (2015)
The african-Brazilian fashion is able to associate, incorporate images and closer, people and objects, and therefore valuing vivencias constructing identities through the appropriation and renewal of material and symbolic goods. The aim of this study is to expose what are the features and objects that identify the african-Brazilian fashion by Brazilian designers that reinforce this style as cultural identity. The methodology was performed through a literature review and qualitative interviews with designers active in the african-Brazilian fashion industry. Research indicates that African stylists seeking ethnic references in ancestors to develop the african-Brazilian fashion, mainly focused on the factors associated with religiosity. Among the most used elements highlight the geometric, wide modeling, variety of colors especially in vibrant colors ,the use of turbans and moorings, especially the sweat cloth coast, kept as ethnic reference on african-Brazilian fashion by designers.